The interdecadal Pacific oscillation drives an extratropical tripole pattern in northern hemisphere summer rainfall anomalies - Zichen Tang; Song Yang; Noel Keenlyside; Lingling Suo; Hanjie Fan; Qingquan Li; Guillaume Gastineau; Tian Tian (Atmospheric Research, 2026)

Unintentional Weight Loss as a Predictor of Adverse Prognosis in Older Adults With Chronic Obstructive Pulmonary Disease in the Intensive Care Unit: A Retrospective Cohort Study - Hongtao Cheng; Yonglan Tang; Shanyuan Tan; Simeng Song; Jia-Ming Xiong; Xiaxuan Huang; Yitong Ling; Zichen Wang; Fuling Zhou; Jun Lyu (Journal of the Academy of Nutrition and Dietetics, 2026)

Spring extreme heat in the Indochina Peninsula enhances the prediction skill of summer precipitation in Central China - Yihua He; Wei Lou; Cheng Sun; Menghao Dong; Zichen Song; Linfeng Shi; Yibing Tong (Atmospheric Research, 2026)

Seasonal dynamics of Gulf Stream–Kuroshio SST coupling: the role of hemispheric atmospheric teleconnections - Menghao Dong; Cheng Sun; Linfeng Shi; Wei Lou; Zichen Song; Yihua He; Yibing Tong (Climate Dynamics, 2026)

Identification of volatile and non-volatile components of two lemons based on sensory characteristics, electronic sensing evaluation and untargeted metabolomics - Baogan He; Long Wan; Zengyi Song; Zichen Ni; Xutong Xiang; Luqi Yin; Binbin Wei; Liming Zhang; Xiaofan Wang (Food Control, 2026)

Predicting soil cadmium spatial distribution with HDXRF coupling to multi-model machine learning in the karst area - Zichen Gu; Hongyan Liu; Xue Mei; Longhua Wu; Ghulam Rasool; Xuexian Li; Yonglin Chen; Hai Zhang; Chunyan Li; Wei Song (Environmental Monitoring and Assessment, 2026)

Changes in persistent anticyclonic circulation across Eurasian continent and its linkage with extreme heatwaves - Yibing Tong; Cheng Sun; Wei Lou; Menghao Dong; Linfeng Shi; Zichen Song; Yihua He (Global and Planetary Change, 2026)

A novel Pac-Man structured Cu-Fe bimetallic catalyst for enhanced PAA activation: Unveiling the critical role of sulfur species in tetracycline hydrochloride degradation - Zichen Cao; Yan Zhao; Qingqing Li; Fanyue Meng; Mengzhu Yu; Songshan Cao; Guanghong Sheng; Dongdong Ren; Bing Song (Journal of Environmental Management, 2025)

Dynamic sealing mechanisms of drilling fluid in fractured coalbed methane formations: a coupled CFD-DEM numerical study - Zichen Han; Xianyu Yang; Ni Ren; Jiwei Song; Meng Zhao; Man Xue; Mengjia Liang; Xinmin Yan; Chunzheng Jin; Guosheng Jiang; Jihua Cai (Computers and Geotechnics, 2025)

Efficient biosorption of molybdenum (VI) using Chlorella pyrenoidosa biomass: Mechanistic insights and sustainable application in water remediation - Zhixin Song; Lingfang Cui; Xunan Li; Zichen Zhang; Chao Zhang; Gangfu Song; Yu Zhao; Wenzhong Tang (Journal of Cleaner Production, 2025)

Evaluating the contribution of residential coal combustion to atmospheric nitrous acid (HONO) in winter - Yang Wang; Pengfei Liu; Chenglong Zhang; Chaoyang Xue; Xiaoxi Zhao; Shuang Fu; Zichen Wu; Yifei Song; Yuzheng Wang; Chengtang Liu; Yujing Mu (Environmental Pollution, 2025)

Abrupt vapor pressure deficit changes over Northeast Asia during 1990s linked to combined Mediterranean-Pacific SST shifts - Zichen Song; Cheng Sun; Dong Xiao; Menghao Dong; Wei Lou; Linfeng Shi (Atmospheric Research, 2025)

Mask-GK: An efficient method based on mask Gaussian kernel for segmentation and counting of grape berries in field - Canchen Yang; Tianyu Geng; Jian Peng; Chun Xu; Zichen Song (Computers and Electronics in Agriculture, 2025)

Assessing the growth dynamics of Listeria monocytogenes and microbiota in RTE poultry: A combined BP-ANN and traditional approach - Zichen Deng; Wenqian Li; Yihuan Song; Hongyi Wen; Yongxian Zhang; Yan Du; Yan Wang; Can Huang; Jingyu Chen (International Journal of Food Microbiology, 2025)

Global teleconnection of concurrent dry and wet events revealed by climate network - Menghao Dong; Cheng Sun; Wei Lou; Linfeng Shi; Zichen Song; Yihua He; Yibing Tong (Climate Dynamics, 2025)

Microenvironment modulation induced by ethylene-glycol modification enables high activity in selective CO2 electroreduction over lead-based catalysts - Yingying Shu; Zhihao Wang; Zichen Song; Wenqian Wang; Xiaolei Wang; Zhimin Chen; Zhiyu Ren (Chemical Engineering Journal, 2025)

Mechanism insight into sulfidated nano zero-valent iron/biochar activated persulfate for highly efficient degradation of p-chloroaniline - Jingchun Yan; Zihan Guo; Yuyuan Sun; Zichen Yan; Rui Liu; Yudong Chen; Jing Song (Chemosphere, 2025)

The reaction mechanism and application of advanced oxidation of peracetic acid: A review - Zichen Cao; Qingqing Li; Fanyue Meng; Bing Song; Guanghong Sheng (Journal of Environmental Chemical Engineering, 2025)

Novel colorimetric-fluorescent dual-mode biosensing platform for detecting acetylcholinesterase and screening acetylcholinesterase inhibitors based on trimetallic nanozymes - Meie Zheng; Mingxing Liu; Fei Ma; Zichen Song; Hongda Zhu; Huiling Guo; Hongmei Sun (Chemical Engineering Journal, 2025)

Bonding interlocked polyaniline with hydrated vanadium oxide for dynamic thermal radiation regulators - Zichen Ren; Dongqi Liu; Leipeng Zhang; Bo Wang; Shanshan Song; Tingting Hao; Yike Zhang; Jiupeng Zhao; Yao Li (Chemical Engineering Journal, 2025)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Rapid-response electrochromic devices with self-wrinkling polyaniline for enhanced infrared emissivity modulation - Yike Zhang; Dongqi Liu; Zichen Ren; Wenchao Liu; Bo Wang; Shanshan Song; Tingting Hao; Lei Xu; Haoyu Ji; Jiawu Sun; Leipeng Zhang; Yao Li (Chemical Engineering Journal, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Unravelling spatiotemporal patterns in global sea surface temperatures with dynamic mode decomposition - Menghao Dong; Cheng Sun; Tian Wei; Zijing Guo; Wei Lou; Zichen Song; Linfeng Shi (International Journal of Climatology, 2024)
Extracting global sea surface temperature (SST) patterns is essential for understanding climate variability in both regional and global perspective. Traditional methods, limited by assumptions of orthogonality, hinder our ability to fully capture the dynamics of global SST, particularly in the complex Pacific basin. This study introduces dynamic mode decomposition (DMD), a powerful method from fluid dynamics, to extract global SST patterns since 1900. Our analysis shows that DMD successfully captures well‐known patterns like global warming and the Atlantic Multidecadal Oscillation (AMO). More importantly, it reveals three Pacific SST modes that are spatially non‐orthogonal but exhibit distinct characteristics. Spectral analysis shows that these Pacific modes have distinct periodicities: Pacific Multi‐decadal Mode (PMDM, ~50 years), Quasi‐decadal Mode (PQDM, 8–16 years) and Interannual Mode (PIAM, 2–8 years). This highlights DMD's strength in not only capturing known patterns but also separating modes with similar spatial features but unique dynamics. Further analysis reveals significant differences in their impacts on global air temperature. During positive phases, all three modes induce tropical warming, with PIAM exerting the strongest influence and PMDM the weakest. In the Northern Hemisphere, both PQDM and PIAM drive mid‐latitude cooling and high‐latitude warming, with a more pronounced effect from PQDM. PMDM, in contrast, triggers widespread cooling across the Northern extratropics. In the Southern Hemisphere, PMDM's influence on temperature exhibits a distinct latitudinal banding pattern. PIAM and PQDM, on the other hand, exhibit a regionalized impact, primarily concentrated in the Amundsen and Ross Seas, with PQDM's influence extending to the Antarctic continent.

Probability map-based grape detection and counting - Canchen Yang; Tianyu Geng; Jian Peng; Zichen Song (Computers and Electronics in Agriculture, 2024)

Simulating liquefaction-induced resuspension flux in a sediment transport model - Zichen Zhu; Xing Du; Bingchen Liang; Linfeng Wang; Yupeng Song; Ping Li; Yaoshen Fan; Shuhua Bian; Yongzhi Wang; Yongqiang Zhang; Bing Li (Water Research, 2024)

Characteristics analysis of leakage diseases of Beijing underground subway stations based on the field investigation and data statistics - Hua Peng; Yujie Li; Xiaokai Niu; Haidong Tang; Xue Meng; Zichen Li; Kuangdi Wan; Wei Li; Wei Song (Transportation Geotechnics, 2024)

A facile and on-demand optimizing strategy for polyurethane elastomers via programmable hydrogen bonding - Zichen Bai; Xiaodong Li; Tianhao Wu; Hao Jiang; Xudong Zhang; Lichen Zhang; Yi Yang; Shuang Liu; Lisha Lei; Ningning Song; Zhengdi Wang; Xing Su; et al. (Chemical Engineering Journal, 2024)

Interhemispheric propagation of seasonal sea surface temperature fluctuations over the western Pacific in CMIP6 - Tian Wei; Cheng Sun; Zijing Guo; Wei Lou; Zichen Song; Linfeng Shi; Menghao Dong (International Journal of Climatology, 2024)
Interannual sea surface temperature (SST) variability in the western Pacific is a critical research topic in climate change, as it can significantly impact regional and global weather patterns. Previous observational studies have shown that SST in the southwestern Pacific (SWP) can effectively serve as a precursor signal for SST in the western tropical Pacific (WTP). In this study, we evaluate and compare the modelling capabilities of 32 CMIP6 models to simulate the relationship between SWP and WTP SST. The results indicate that while some CMIP6 models can simulate the spatial connection and physical processes between the SWP and WTP, there are significant intermodel differences. Specifically, the models that best simulate the cross‐equatorial propagation of SWP SST anomalies are those that accurately simulate the cross‐equatorial wind anomalies induced by SWP SST anomalies, highlighting the key role of wind‐evaporation‐SST feedback in SST propagation. Further analysis reveals that the intermodel spread in cross‐equatorial SST propagation is attributable to model biases in simulating climatological SST and wind speed. Models with warm climatological equatorial SST and strong wind speeds provide favourable conditions for the cross‐equatorial propagation of SWP‐related SST anomalies towards the north. Warm SST and strong inter‐season wind speeds near the equator facilitate the northward propagation of the SWP warm signal, leading to increased warming in the WTP.

Defects engineering and interface regulation on nickel-rich sulphides promoting water/urea/ethanol electrooxidation - Xuan Zhang; Xianchao Wang; Qing Yan; Ruiqin Gao; Jing Zhao; Zichen Song; Kai Zhu; Dianxue Cao; Jiaxin Yao; Lingwei Zheng; Guiling Wang (Chemical Engineering Journal, 2024)

A novel competitive fluorescence colorimetric dual-mode immunosensor for detecting ochratoxin A based on the synergistically enhanced peroxidase-like activity of AuAg NCs-SPCN nanocomposite - Chenxi Ke; Yu Wu; Zichen Song; Meie Zheng; Hongda Zhu; Huiling Guo; Hongmei Sun; Mingxing Liu (Food Chemistry, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Bio-inspired thermal actuator for dynamic multispectral modulation from visible to microwave wavelengths - Shanshan Song; Gaoping Xu; Tingting Hao; Zichen Ren; Dongqi Liu; Yike Zhang; Jiupeng Zhao; Leipeng Zhang; Yao Li (Chemical Engineering Journal, 2024)

Relationships between structural design and synthesis engineering of Cu-based catalysts for CO2 to C2 electroreduction - Zichen Song; Xiaolei Wang; Zhiyu Ren; Honggang Fu (Chemical Engineering Journal, 2024)

Interface-induced enhancement of paired electrolysis in 5-hydroxymethylfurfural-H2O system on symbiotic nickel/molybdenum nitride heterostructure - Siyu Ma; Zhihao Wang; Bowen Liu; Xiaolei Wang; Shichao Du; Zichen Song; Xinxin Bian; Manchen Hao; Ju Huang; Zhimin Chen; Zhiyu Ren (Chemical Engineering Journal, 2023)

Enhancing infrared electrochromic properties of the poly(styrene sulfonate) doped polyaniline composite film by morphology regulation - Leipeng Zhang; Tingting Hao; Shanshan Song; Bo Wang; Dongqi Liu; Zichen Ren; Wenchao Liu; Yike Zhang; Gaoping Xu; Xiangqiao Yan; Yuan Lu; Yao Li (Chemical Engineering Journal, 2023)

From Geoparks to Regional Sustainable Development: Geoheritage Protection and Geotourism Promotion of Geoparks in Hebei Province, China - Yanjie Wang; Xiuming Li; Zichen Han; Jinfang Han; Xiaoxiao Pang; Wenli Song; Qinpeng Wang (Geoheritage, 2023)

Regulating tumor cholesterol microenvironment to enhance photoimmunotherapy in oral squamous cell carcinoma - Chuanhui Song; Xinyu Zhang; Zichen Cao; Zheng Wei; Meng Zhou; Yufeng Wang; Shengwei Han; Yu Cai; Wei Han (Chemical Engineering Journal, 2023)

Extracorporeal shock wave therapy decreases the number of total and degranulated mast cells and alleviates pelvic pain in a rat model of prostatitis - Zhengyao Song; Chen Jin; Zichen Bian; Chaozhao Liang (Molecular and Cellular Biochemistry, 2021)

The complete genome sequence of Escherichia phage SRT7, a novel T7-like phage - Kaili Zhao; Shukai Song; Zhipeng Zhao; Zichen Liu; Yan Ji; Pengfei Gu; Xiangyu Fan; Qiang Li (Archives of Virology, 2019)